2020
DOI: 10.3389/fmicb.2020.00642
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity, Characteristics, and Public Health Implications of Listeria monocytogenes in Ready-to-Eat Foods and Pasteurized Milk in China

Abstract: Listeria monocytogenes is a foodborne pathogen with a high mortality rate in humans. This study aimed to identify the pathogenic potential of L. monocytogenes isolated from ready-to-eat (RTE) foods and pasteurized milk in China on the basis of its phenotypic and genotypic characteristics. Approximately 7.7% (44/570) samples tested positive for L. monocytogenes among 10.8% (39/360) RTE and 2.4% (5/210) pasteurized milk samples, of which 77.3% (34/44) had < 10 MPN/g, 18.2% (8/44) had 10-110 MPN/g, and 4.5% (2/44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…The L. monocytogenes strains in the present study revealed that ST8 was the most prevalent ST from samples of RTE vegetables and pork pĂątĂ©. The ST8 has been found in different RTE foods such as meats, salmon, cooked meats, fried rice and noodles, and vegetables ( Wang et al, 2015 ; Ziegler et al, 2018 ; Chen et al, 2020b ). In addition, ST8 has been responsible for cases of human listeriosis in Canada, Italy, Switzerland, and Germany ( Knabel et al, 2012 ; Mammina et al, 2013 ; Althaus et al, 2014 ; Ruppitsch et al, 2015b ; Halbedel et al, 2020 ), and it has been considered to have high pathogenic potential ( Fagerlund et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The L. monocytogenes strains in the present study revealed that ST8 was the most prevalent ST from samples of RTE vegetables and pork pĂątĂ©. The ST8 has been found in different RTE foods such as meats, salmon, cooked meats, fried rice and noodles, and vegetables ( Wang et al, 2015 ; Ziegler et al, 2018 ; Chen et al, 2020b ). In addition, ST8 has been responsible for cases of human listeriosis in Canada, Italy, Switzerland, and Germany ( Knabel et al, 2012 ; Mammina et al, 2013 ; Althaus et al, 2014 ; Ruppitsch et al, 2015b ; Halbedel et al, 2020 ), and it has been considered to have high pathogenic potential ( Fagerlund et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lm _2541 also carried LIPI-4, a six genes cluster, encoding for a cellobiose-type phosphotransferase system, recently identified ( Maury et al., 2016 ). LIPI-4, highly prevalent in CC4, enhances invasion and in particular, neural and placental tropism of Lm , resulting in a strong association of this virulence factor with neural and placental infections ( Maury et al., 2016 ; Chen et al., 2019 ; Chen et al., 2020 ). Therefore, infection-associated isolates harboring LIPI-4 are typically considered hypervirulent.…”
Section: Discussionmentioning
confidence: 99%
“…Montero et al [ 25 ] and Vilchis-Rangel et al [ 38 ] reported similar percentages (20–40%) for LIPI-1 in L. monocytogenes isolates from orange juice, vegetables, and frozen vegetables. Moreover, several studies have reported LIPI-1 in 100% of L. monocytogenes isolates from duck, beef, pork, chicken, vegetables, fried rice, fish, goat meat, pasteurized milk, and yogurt [ 13 , 39 , 40 ]. The wide range of virulence-associated L. monocytogenes genes found in this study could be associated with food type, sources, mechanisms of contamination during food processing and marketing, epidemiological factors, countries, geographical differences, the genetic diversity of strains, and methodologies for the serotyping of L. monocytogenes in food.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the virulence potential of L. monocytogenes is important in terms of public health, as is risk identification in ready-to-eat (RTE) fruits and vegetables because they provide critical information regarding food sources of listeriosis [ 13 ]. Currently, L. monocytogenes consists of four major evolutionary lineages (I, II, III, and rare lineage IV), including 14 recognized serotypes of L. monocytogenes that are grouped into four PCR serogroups [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation